A linear sweep voltammetric determination of proteins with thorin - Sun, Wei (Acta chimica slovenica, 2006)
In pH 3.0 acidic buffer solution, 2-(2-hydroxy-3,6-disulfo-1-naphthyl)-azo-phenylarsenic acid (thorin) can interact with protein to form a supramolecular complex. The interaction of thorin with human serum albumin (HSA) was studied in solution by cyclic voltammetry on mercury electrode. In the presence of HSA, the reductive peak current of thorin at -0.49 V (vs.SCE) was decreased apparently without the changes of peak potentials and no new peaks appeared. The electrochemical parameters of the thorin-HSA interaction solution were calculated and compared with that of thorin solution, the results showed that there were no obvious differences in the two sets of parameters. So the formed biosupramolecular complex was electrochemical inactive and couldn't take place redox reaction on the mercury electrode. The binding reaction resulted in the decrease of the free concentration of thorin in the reaction solution, and the decrease of the reductive peak current of thorin. The binding constantand the binding ratio of thorin-HSA were calculated as 1.15*109 and 2:3, respectively. Based on the decrease of peak current, a sensitive protein assay method was proposed with second order derivative linear sweep voltammetry. The optimal conditions such as the effect of pH, the concentration of thorin, reaction time and temperature, ionic strength et al on the binding reaction had been carefully studied. The interference of coexisting substances was checked. Under the selected conditions, the decrease of the reductive peak current of thorin was in proportion to the concentration of 1.0~12.0 mg L-1 for HSA, 0.1~16.0 mg L-1 for bovine serum albumin (BSA), 1.0~20.0 mg L-1 for oval albumin (OVA) and 0.4~18.0 mg L-1 for lipase et al. This new electrochemical method was further applied to the determination of human serum samples and the results were in good agreement with the traditional Commassie Brilliant Blue G-250 (CBB G-250) spectrophotometric method.
Keywords: analizna kemija; biokemija; ciklična voltametrija; človeški serum; elektrokemične metode; elektrokemija; interakcije; proteini; torin